The Development of Numeration-Based Curriculum Merdeka Learning Module for Students of Madrasah Tsanawiyah in North Aceh : Development of Numeration-Based Curriculum Merdeka Learning Module - Fajriana Fajriana; Siraj Siraj; Yulia Zahra; Rizka Sulaiha; Syafirly Syafirly (LPPM Universitas Malikussaleh, 2024)
Developing numeracy-based teaching modules within the Merdeka Curriculum framework at MTsN aims to improve students' mathematics skills independently and contextually. This module is designed to support more flexible learning according to student's needs and interests while preparing them to face academic and daily life challenges. The numeracy approach in this module involves integrating mathematical concepts into various subjects and real situations. So that students can apply their numerical skills effectively in multiple contexts. In addition, this module is also equipped with various innovative learning strategies, including project-based learning, the use of technology, and formative assessment. Through the development of this numeracy-based teaching module, it is hoped that students can develop critical thinking, problem-solving, and decision-making skills, which are very much needed in the current era of globalization and digitalization. Implementing this module is also expected to support teachers in teaching relevant and engaging materials and improve the quality of education at the MTsN level. The objectives of this study were to determine the feasibility of the teaching module instrument and the practicality and effectiveness of the teaching module. The development model used in this research is the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation).